Concentration and extermination camps in the Independent State of Croatia: war and genocide, 1941-1945 - Fernández Pasalodos, Arnau; Rodrigo Sánchez , Javier (Cuadernos de Historia Contemporánea, 2023)
Abstract. The Spanish historiography of the concentration and extermination camps of the 1930s and 1940s has focused its attention on the Franco and Hitler regimes. However, during World War II there were other places where other states created their own concentration camps, including the Independent State of Croatia. Between 1941 and 1945 the fascist regime led by Ante Pavelić and the Ustaša established more than a dozen concentration and extermination camps to confine men, women and children for ethnic, religious and political reasons. For this reason, the concentration and extermination camps became the epicenter of the genocide perpetrated against Serbs, Jews and Gypsies. In addition, these prison spaces were also used in the framework of the antipartisan war against the parties led by Tito, at the same time that they were used to lock up any political dissident.